The Making of a Mosque with Female Imams Serendipities in the Production of Danish Islams - Petersen, Jesper (Brill, 2022)
In the last decade a number of women-led mosques have emerged in Europe and North America. In The Making of a Mosque with Female Imams Jesper Petersen documents the serendipitous, yet predictable, emergence of the Mariam Mosque in Copenhagen. The study first demonstrates that individuals' facing the unpredictable plays a decisive role in social processes. This leads to an investigation of how serendipities are erased when narratives are erected retrospectively in the form of commodified products, autobiographical narratives, and research. Furthermore, Petersen conceptualizes non-Muslims' theological productions of Islam - Islam without the worship of Allah, so to speak - and demonstrates how this influences Muslim productions of Islam.